A new species of Physomerus Burmeister (Hemiptera: Heteroptera: Coreidae: Coreinae), with a key to the species of India - Mukherjee, Paramita; Hassan, M. E.; Biswas, B. (Zootaxa, 2016)
A new species from India, Physomerus centralis sp. nov. (Hemiptera: Heteroptera: Coreidae) is described and illustrated with both male and female genitalia. Morphological measurements and their ratios were taken as additional diagnostic characters. A key to the Indian species of the genus Physomerus Burmeister is provided.